Anatomy as an Emerging Science and Career Option in View of Medical Students in Bangladesh (Bangladesh Journal of Anatomy, 2010)
Three hundred and thirty four medical students were questioned regarding their views on anatomy as an emerging science and further career option. A questionnaire with 16 statements was given to these students and their answers were compiled. The results of this study were encouraging. 99% of students consider anatomy as an essential pillar of medical science. A vast majority (94%) felt that a sound knowledge of anatomy helped them in their clinical term. However, more than 50% termed anatomy was difficult to understand and more than two-third agreed to the question that the duration of teaching anatomy should not be limited to one and a half year. Though 73% placed anatomy apart with clinical subjects. More than 80% compared teaching anatomy as favorable as treating a patient. In Bangladesh, lack of satisfactory job opportunities and adequate research facilities limits the uptake of anatomy as a career option. Even with a modified curriculum two third were willing to become an anatomist. A formal course in teaching was welcomed by most in case they sought to become anatomist. Key words: Anatomy; an emerging science; career option; students view. DOI: 10.3329/bja.v8i1.6106 Bangladesh Journal of Anatomy January 2010, Vol. 8 No. 1 pp. 28-33